2022
DOI: 10.33772/jsipi.v6i2.15
|View full text |Cite
|
Sign up to set email alerts
|

Sistem Pengelolaan Perikanan Demersal di Karang Kapota Taman Nasional Wakatobi

Abstract: Kondisi perikanan demersal di perairan Taman Nasional Wakatobi (TNW) pada zona pemanfaatan khususnya di Karang Kapota bisa dinyatakan padat tangkap, sehingga perlu dilakukan suatu penelitian mengenai perencanaan dan pengembangan perikanan demersal melalui pendekatan sistem untuk mengurai permasalahan yang terjadi. Penelitian ini bertujuan untuk mengidentifikasi karakteristik perikanan demersal, menganalisis stakeholders yang terlibat, dan mendesain sistem pengelolaan perikanan demersal di Karang Kapota TNW. Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
0
0
Order By: Relevance
“…Then, the score of five questions is added up and mapped in the form of an interest and influence matrix. The determination of scores on questions to measure the level of interest and influence of stakeholders refers to five-level data measurement (Abbas 2005;Hasan et al 2022), as shown in Table 1. The results of the stakeholders categories based on their interests and influences are grouped into four quadrants, as presented in Fig.…”
Section: Stakeholders' Categories Based On Interest and Influencementioning
confidence: 99%
“…Then, the score of five questions is added up and mapped in the form of an interest and influence matrix. The determination of scores on questions to measure the level of interest and influence of stakeholders refers to five-level data measurement (Abbas 2005;Hasan et al 2022), as shown in Table 1. The results of the stakeholders categories based on their interests and influences are grouped into four quadrants, as presented in Fig.…”
Section: Stakeholders' Categories Based On Interest and Influencementioning
confidence: 99%